Animal Research Biosafety. (September 2018) - Alderman, T. Scott; Carpenter, Calvin B.; McGirr, Rebecca
The use of laboratory animals as experimental models of disease has been a critical tool for biomedical researchers for decades. Animal studies allow scientists to discover and understand the mechanism of infection and ultimately to develop effective treatment and prevention modalities. Workers who directly handle infectious microbes or infected laboratory animals are at risk of exposure while performing their assigned duties. A comprehensive biosafety program, led by a biosafety professional, is critical to properly protect workers and the surrounding community. Such a program includes a thorough understanding of the biohazard through formal risk assessment, implementation of effective biohazard controls, and extensive training of all personnel who are at risk of exposure.